Editorial - The new: restless and frightening, it is the most seductive and difficult path - CARLOS ALBERTO FIGUEIREDO DA SILVA (Universidade Salgado de Oliveira, 2021)
The new: restless and frightening, it is the most seductive and difficult path. The paths of humanity are being generated from the indeterminate, the unforeseen, the unusual; this takes us to think then: why manage, plan, anticipate? In all our years of experience in the sports field, we seek to build scenarios, analyze external and internal environments, and use management tools. Perhaps the appropriate metaphor to represent all these cycles is the Olympics. History shows us the strength of the cyclical element in our existence as a species and people in the sports group. We organize, train, guide, plan from them. But suddenly, something happens that seems to contradict our cyclical experience. Unpredictability, non-substantiality, non-essentiality are elements dealt with in various spheres but hardly in management. Some authors try to find explanations by constructing other metaphors, such as the "black swan". Post-structuralists, post-critics, post-moderns work with dispersion. I think we can leave the throne of the strategists and, in the face of this perplexed-complex-context, abandon the strategy and develop tactical aspects, as Certeau tells us, capturing the opportunities on the flight. So, as the coach, on the edge of the court, when he sees his strategy crumble, look for what it does, solutions to continue moving forward with his team. Thus, like the boy from the favela, by imitating the verbal and corporal codes of the traffickers, he builds ontological security, as taught by Giddens, which allows him to move around in that environment, avoiding being harassed, beaten, or killed. So, as Sarmento inspires us: "little boy what are you capable of? Do what is done or invent what never existed?". It is in this imbroglio that RIGD advances to its eleventh year of existence in a pandemic that haunts us. The participants of the RIGD project do not tire of believing in a dream that appears in Lusophony but has received support from the intercontinental brothers. From this first issue of 2021, we will have the doi (digital object identifier), which will give more visibility to the journal's articles. We are awaiting Scopus' evaluation. We partner with ABEC (Brazilian Association of Scientific Publishers) and Crossref. We have a long way to go. If our organic experience ends and we return to the mineral kingdom, the team is formed, as RIGD is a collective project.